Mary Douglas a very personal method : anthropological writings drawn from life - Fardon, Richard (Sage, 2013)
Mary Douglas was one of the most regarded anthropologists of the 20th Century. This is a dynamic and very personal collection of her reflections upon anthropological and cultural method within the social sciences.